DESIGN OF EMPLOYEE SALES APPLICATION USING GROSS UP METHOD IN CV. NUSANTARA ELECTRONIC SERVICES BASED ON DESKTOP - Jidny Ilma Mochamad; Anjik Sukmaaji; arifin puji widodo (Jurnal Sistem Informasi Universitas Dinamika, 2020)
CV. Nusantara Services Electronics is a company electronic services in fulfilling the needs of consumer support. Problems arising in this integrated information need by the parties-related parties in the recapitulation of employee payroll. The effects caused by payroll system are not integrated in the system that is the occurrence of data buildup that causes employee salaries to experience delays in payment.Based on the problem above, it is made to be designed to build payroll employee application that can produce the calculation of presences, employee debts, allowances, BPJS, PPh 21, and net salary to complete and facilitate the related parties Paying employee salaries.The system generates recap attendance information, loan recording, and processing of tax, salary and Bpjs calculations that can be used to assist the company in paying employee salaries.